Targeted Delivery of Chemo‐Sonodynamic Therapy via Brain Targeting, Glutathione‐Consumable Polymeric Nanoparticles for Effective Brain Cancer Treatment. Issue 28 (15th August 2022) - Wu, Haoan; Gao, Xingchun; Luo, Yuanyuan; Yu, Jiang; Long, Gretchen; Jiang, Zhaozhong; Zhou, Jiangbing
Abstract: Glioblastoma (GBM) is the most aggressive tumor of the central nervous system and remains universally lethal due to lack of effective treatment options and their inefficient delivery to the brain. Here the development of multifunctional polymeric nanoparticles (NPs) for effective treatment of GBM is reported. The NPs are synthesized using a novel glutathione (GSH)‐reactive poly (2, 2″‐thiodiethylene 3, 3″‐dithiodipropionate) (PTD) polymer and engineered for brain penetration through neutrophil elastase‐triggered shrinkability, iRGD‐mediated targeted delivery, and lexiscan‐induced autocatalysis. It is found that the resulting lexiscan‐loaded, iRGD‐conjugated, shrinkable PTD NPs, or LiPTD NPs, efficiently penetrate brain tumors with high specificity after intravenous administration. Furthermore, it is demonstrated that LiPTD NPs are capable of efficient encapsulation and delivery of chemotherapy doxorubicin and sonosensitizer chlorin e6 to achieve combined chemotherapy and sonodynamic therapy (SDT). It is demonstrated that the capability of GSH depletion of LiPTD NPs further augments the tumor cell killing effect triggered by SDT. As a result, treatment with LiPTD NPs effectively inhibits tumor growth and prolongs the survival of tumor‐bearing mice. This study may suggest a potential new approach for effective GBM treatment. Abstract : Glutathione (GSH)‐reactive polymer‐based nanoparticles (NPs), which can target drug delivery to the brain tumor through the integration of neutrophil elastase‐triggered shrinkability, ligand‐mediated interaction, and lexiscan‐induced blood–brain barrier modulation. The resulting NPs with excellent penetration capability can efficiently deliver chemotherapy drug doxorubicin and sonosensitizer chlorin e6 to tumors in the brain for effective chemo‐sonodynamic combination therapy.